The Effect of Direct and Indirect Corrective Feedback on Students' Spelling Errors - Sasan Baleghizadeh; Mehdi Dadashi (Universidad Nacional de Colombia, 2011)
The study presented here is an attempt to examine the role of indirect feedback in promoting junior high school students' spelling accuracy in English. It compares the effect of direct feedback with indirect feedback on students' written work dictated by their teacher from their textbooks. Two classes were selected from the Zanjanrood District in Iran. Forty-four male students in two groups, one from School A (the direct feedback group) and the other from School B (the indirect feedback group) were treated differently regarding their spelling errors for six weeks. The results obtained revealed that indirect feedback is a more effective tool than direct feedback in rectifying students' spelling errors.